1966
DOI: 10.1111/j.1471-4159.1966.tb07512.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Energy Reserves in Mouse Brain and Changes With Ischaemia and Anaesthesia*

Abstract: WHEN the blood supply to the brain is cut off, function may be maintained for a short time through utilization of the energy reserve. This reserve has only four major components, P-creatine, ATP, glycogen, and glucose. Consequently the rates of change of these four substances during brief periods of complete ischaemia should be a valid measure of metabolic rate. Studies of whole brain (LOWRY, PASSONNEAU, HASSELBERGER and SCHULZ, 1964) and nerve (STEWART, PASSONNEAU and LOWRY, 1965) indicate this to be true. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
2

Year Published

1968
1968
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(47 citation statements)
references
References 1 publication
2
43
2
Order By: Relevance
“…Table III compares the present data with comparable published data. It is likely that the difference between the present results and those of Lowry et al (9)(10)(11) are largely due to the smaller head size in the mouse and differences in freezing technique.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…Table III compares the present data with comparable published data. It is likely that the difference between the present results and those of Lowry et al (9)(10)(11) are largely due to the smaller head size in the mouse and differences in freezing technique.…”
Section: Resultscontrasting
confidence: 55%
“…The high brain glucose in the uremic rat merely reflects the fact that a slower rate of glucose consumption will permit brain glucose to more closely approach blood glucose during life. A marked increase of brain glucose is also seen in anesthesia and the extent of this increase has led others to suggest that, in addition to a decreased glucose consumption in anesthesia, there may be a primary increase of transport of glucose into brain (10,11). An increase in the extracellular fluid volume of brain in anesthesia and uremia could also produce a high brain glucose.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, animal anesthesia, and the time period following animal death greatly affect localized lactate concentration. 21,70 Therefore, the lactate observed within the Purkinje neuron in this investigation may not reflect an in vivo state, but rather one induced during animal anesthesia and death. A thorough investigation of how sample preparation effects lactate concentration, and other biochemical markers effected by hypoxia-ischemia, which can be detected with novel spectroscopic techniques (i.e., FTIR, XAS, XRF), has been undertaken by this research group, and will be reported in a separate manuscript.…”
Section: 61−69mentioning
confidence: 99%
“…ATP, P-creatine, and glucose were assayed by the methods of Lowry et al [lo]. Lactate and glycogen were measured by the methods of Gatfield et al [4]. For the determination of concentrations of glucose in the blood, samples of heparinized plasma were diluted 10-20 times in 0.5 M perchloric acid and centrifuged at 4".…”
Section: Preparation Of Blood and Tissue Extracts And Methods Of Assamentioning
confidence: 99%